Next-generation sequencing panel test results in pediatric patients with progressive familial intrahepatic cholestasis: a single-center experience - Topak, Ali (The European Research Journal, 2023)
Objective: The aim of this study is to reveal the diagnostic yield of the progressive familial intrahepatic cholestasis (PFIC) gene panel that we have used in the diagnosis of this patient group, which accounts for approximately 10% of cholestatic liver disease, and to report the clinical findings of our patients with the detected variants. Methods: In this study, we retrospectively evaluated the results of molecular genetic analysis of pediatric patients whose PFIC gene panel contained the ATP8B1, ABCB11, and ABCB4 genes. Results: In 10 patients, 12 different variants were detected that could explain the PFIC clinical picture. Three of these variants were considered novel variants. Conclusion: Our study demonstrates the usefulness of the NGS panel in diagnosing pediatric patients with PFIC findings. This diagnostic method also contributed to the variant spectrum of PFIC-related genes.